الاستثمار في تقنية الإنتاج الأنظف في الصناعة السورية - صقر, أديب (Latakia University Journal - Economic and Legal Sciences Series, 2018)
The application of cleaner production in a national industry is necessary steps to adopt the environmental and economic dimension in the process of manufacturing. Cleaner production is in the beginning of the process of manufacturing,. Cleaner production is advanced technology designed to preserve the environment and ensuring economic profitability and improve the quality of the product through its transformation into a product of economic and environmental specifications, thus making it competitive as a in the domestic and foreign markets, and improving the environment and ensure rational use of economic resources .so use technology of Cleaner production in national industry have economic and environmental benefits by reducing of the production and environmental costs because it relies on the principle of bringing raw materials and most advanced technology and cleaner. this paper has studied the the economic important of investment in technology of cleaner production in syiran industry, so,studied the concept of cleaner industrial production , and the means to achieve cleaner production . In addition to this the search discusses the environmental and economic beneficial of applying this technology and the possibilities of applying it in Syria , and Study of the process of successful experiences in the application of cleaner production technology. يعد تطبيق تقنية الإنتاج الأنظف في الصناعة الوطنية إحدى الخطوات الضرورية لتبني البعد البيئي والاقتصادي في العملية التصنيعية.حيث أن الإنتاج الأنظف يحتاج إلى تكنولوجيا متطورة تهدف إلى الحفاظ على البيئة وضمان الربحية الاقتصادية والاجتماعية وتحسين جودة المنتج من خلال تحويله إلى منتج اقتصادي بمواصفات بيئية . وهذا يكسبه صفة تنافسية في الأسواق المحلية والخارجية، فضلاً عن تحسين بيئة العمل وضمان ترشيد استهلاك الموارد الاقتصادية. فتبني تقنية الإنتاج الأنظف في الصناعة الوطنية يحقق فوائد اقتصادية وبيئية مهمة من خلال تخفيض الكلف الإنتاجية والبيئية ، لأنه يعتمد على مبدأ إحلال المواد الخام والتكنولوجيا الأكثر تطوراً والأنظف. يهدف هذا البحث إلى تسليط الضوء على الأهمية الاقتصادية والبيئية للاستثمار في تقنية الإنتاج الأنظف في الصناعة السورية ، حيث نناقش مفهوم الانتاج الصناعي الأنظف ووسائل تحقيقه ، بالإضافة إلى الفوائد الاقتصادية والبيئية من تطبيق هذه التقنية في سورية ، ودراسة بعض التجارب الناجحة في هذا المجال .